A Genre Analysis Of The Difficulties In Writing Descriptive Text By The Students Of Class VIII SMP N 2 Kartasura In 2012/ 2013 Academic Year - Indriyani, Rini Puti; , Drs. Djoko Srijono, M. Hum; , Siti Fatimah, S. Pd., M. Hum (2013)
This research paper is aimed at (1) identifying the difficulties faced by the students in writing descriptive text of class VIII SMP N 2 Kartasura in 2012/ 2013 academic year, (2) describing the solutions to the student's problem in writing descriptive text written by the student of class VIII SMP N 2 Kartasura in 2012/ 2013 academic year. The object of this research is the descriptive text written by the students of class VIII SMP N 2 Kartasura in 2012/ 2013 academic year. The methods of collecting data in this research are as follows; document analysis and interview. From the data of descriptive text written by the students of class VIII SMP N 2 Kartasura, the writer can conclude the difficulties of the students in writing descriptive text and the solutions to the students' problem in writing descriptive text. The difficulties of the students in writing descriptive text, are as follows:1) generic structure, and 2) language features. Then, the English teacher give solutions to the students' problem, as follows: 1) solution to the students' problem in arranging elements of descriptive text, 2) solution to the students' problem in making sentences 3) solution to the students' problem in composing sentences, 4) solution to the students' problem of memorizing the vocabulary, and 5) solution to the students' problem of spelling words in writing descriptive text.